IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH THE FOCUS ON FORM APPROACH - Dea Amanda Putri; Dias Wahyu Rawikarani; Ruslan Hasyim (Journal of English Education, 2026)
This study examined whether the Focus on Form (FonF) approach improved students' speaking ability at the second grade of MAN 2 Barru. The research responded to students limited oral practice, anxiety, grammatical inaccuracy, restricted vocabulary, and hesitation in classroom speaking. A quantitative pre-experimental one-group pre-test and post-test design was applied. Twenty students were selected from the second-grade population through simple random sampling. The instruments consisted of speaking tests and an observation checklist. The treatment used WH-question materials integrated with communicative practice and corrective feedback, including recast, elicitation, metalinguistic clues, clarification requests, and repetition. The findings showed that the students' mean score increased from 30.4 in the pre-test to 62.8 in the post-test. The standard deviation decreased from 7 to 3, indicating more consistent achievement after treatment. The t-test value was 3.19, which was higher than the t-table value of 1.743 at the 5% significance level. The results indicate that FonF significantly improved students' speaking ability, especially in fluency, vocabulary use, pronunciation, and grammatical accuracy.